An Analysis of Accredited Colombian Universities, Based on Performance Variables Associated with Their Quality. Issue 4 (8th August 2022) - Gabalán-Coello, Jesús; Balcero-Molina, Anlly Liced; Vasquez Rizo, Fredy Eduardo; Martínez-González, Adrián; Fonseca-Grandón, Gonzalo
ABSTRACT: This study presents the formulation of a quantitative and qualitative index of quality for accredited institutions based on their performance in five components related to institutional quality: research, students' performance, dropout rates, employability, and accreditation. This index will allow each accredited institution to identify its competences and shortcomings in contrast to the rest, not with the intention of establishing a stiff metrics and positioning system, but of generating information inputs that are flexible and relevant and that allow the revision of each university's status, thus constituting the foundations for a Colombian accreditation observatory for the purpose of continuous improvement.